Assessment of potato peel and agro-forestry biochars supplementation on in vitro ruminal fermentation - Rodrigues, Ana R. F. (2020)
UIDB/50006/2020 UIDB/04033/2020 grant ref. PDE/BDE/114434/2016 DL 57/2016 -Norma transitória.